2020
DOI: 10.3390/f11111211
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of Physiological Events Associated with the Micropropagation of Eucalyptus sp.

Abstract: Micropropagation is a reliable technique in biotechnology and genetic engineering domain, which has been widely applied for rapid mass propagation of plants in vitro condition. Through micropropagation techniques, reproduction of plants can be attained from different explants using organogenesis and somatic embryogenesis. Over the decades, micropropagation techniques have offered tremendous potential for forest tree improvement. Eucalyptus is a woody plant species recalcitrant to in vitro culture. In general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 181 publications
1
16
0
Order By: Relevance
“…The addition of activated charcoal to the culture medium increases the adsorption of substances -such as phenols and ethylene -that inhibit plant development, as well as minimizes the toxicity of plant growth regulators or of exogenous substances with harming effect, which contributes to greater shoots proliferation and explant in vitro growth (SARTOR et al, 2013;ABIRI et al, 2020), as observed in the present study.…”
Section: Activated Charcoal In the In Vitro Multiplicationsupporting
confidence: 58%
See 1 more Smart Citation
“…The addition of activated charcoal to the culture medium increases the adsorption of substances -such as phenols and ethylene -that inhibit plant development, as well as minimizes the toxicity of plant growth regulators or of exogenous substances with harming effect, which contributes to greater shoots proliferation and explant in vitro growth (SARTOR et al, 2013;ABIRI et al, 2020), as observed in the present study.…”
Section: Activated Charcoal In the In Vitro Multiplicationsupporting
confidence: 58%
“…With respect to the negative effects of activated charcoal supplementation, it is possible highlighting the adsorption of growth regulators (auxins and cytokinins), vitamins and of other organic substances important for explant in vitro development and growth. Activated charcoal also naturally releases substances that are found on, or adsorbed by, it (ABIRI et al, 2020;CORBELLINI et al, 2020).…”
Section: Activated Charcoal In the In Vitro Elongationmentioning
confidence: 99%
“…Eucalyptus has tremendous benefits, as this genus has great economic importance due to its fast-growing nature [ 62 ], tolerance to biotic stress conditions [ 5 ], and versatile uses of its essential oils [ 70 ]. Eucalyptus essential oils have aromatic scents and can be extracted from various species of Eucalyptus [ 71 ].…”
Section: Eucalyptus In a General Viewmentioning
confidence: 99%
“…The earliest discussion of the possible consequences of nanotechnology can be traced back to 1986, when Eric Drexler developed some nanotechnology techniques along with other technological advances [ 3 ]. Over the past years, the advances of nanotechnology have been significantly sparked in the fields of medical, agriculture, and forestry [ 4 , 5 , 6 ]. To develop an efficient synthesis of nanoparticles (NPs), different biological, chemical, and physical strategies have been applied [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation